Benefícios obtidos após a implantação de sistemas ERP - Furini, Leandro Rocha (2014)
This qualitative and quantitative research seeks to identify which operational, managerial, technological, strategic, organizational and financial benefits are earned by companies that have implemented ERP systems. Through interviews in 3 companies of electrical, construction and financial sectors, based on literature, we have identified which of the benefits were in fact observed in the companies. This study indicates that ERP brings many of those expected benefits to companies, especially those related to operational, managerial, strategic and organizational issues, but less than expected in matters related to IT. As the interviewed companies did not monitored the financial benefits , a non-parametric analysis of financial ratios about 14 listed companies, before and after the adoption of ERP, allows to identify that ERPs may have contributed to the reduction of corporate profitability, although they have generated improvements management of working capital . This benefit was also identified in the qualitative research, which showed a reduction in cycle time and improves productivity. Other benefits were also highlighted as better control performance, better corporate governance, cost leadership / economies of scale, organizational culture change towards a results focused culture. On the other hand, qualitative research indicated worsening in overall IT costs, in employee motivation and corporate profitability, which confirms the results of quantitative research. Despite the general perception that the implementation of ERPs was beneficial to companies, it was found that the interviewed companies not monitored in a structured way its impact and it’s not possible to say that the benefits outweigh the costs of implementation. Finally, based on the points raised in the literature and interviews, this paper proposes metrics for monitoring the benefits that this can be done in a tangible way in business.